Influence of protein adsorption on tribocorrosion behaviour of CoCrMo biomedical-grade alloys. (October 2020) - Namus, Righdan; Rainforth, W.M.
Abstract: CoCrMo alloys have been widely used in metal-on-metal hip replacements. They exhibit excellent long-term survival rates; however, recently, high failure rates associated with adverse local tissue reactions have been observed. CoCrMo alloys generally work extremely well; however, sometimes their wear rate is high. This work investigated protein adsorption effects on the tribocorrosion behaviour of CoCrMo biomedical-grade alloys under different surface and media conditions. The study of the wear mechanisms indicated that protein adsorption affects the corrosion and mechanical material loss of the investigated material. The synergistic and antagonistic behaviour of the material was correlated with the protein adsorption. Highlights: Considering range of realistic conditions which is found around hip joints including protein concentration in human body fluid and local cathodic polarisation in studying the protein adsorption phenomenon. The influence of the adsorbed proteinaceous layer on tribocorrosion behaviour. The material loss contributions in tribocorrosion are directly affected by protein adsorption phenomenon. Wear rate increased with protein content in the solution only at cathodic potential working condition.